On the Gaggings and Liberations: A Poetics of the Loss in La Noche, by Ennio Moltedo (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
This paper analyzes the poetic of the loss of word in Ennio Moltedo's La Noche (1999). In this text, Moltedo discusses the effects of dictatorship on the structure and utterances of the Chilean language during the post-dictatorial period (from 1990 onwards). The grounding of this paper is based on two parts: (1) lines of capturing, which reduce discourse into a "molar" formation (comparable to a mummified body in which discourse of the post-dictatorial period tends to forming a despotic machine), and, (2) lines of escape to the "polarization", which provide an open space for the recovering and reshaping of utterance.
Keywords: Ennio Moltedo; chilean poetry; dictatorship; post-dictatorship